Aliminary Diseases in Women and its Specific Characteristics (Example of Minerals) - Sattorzoda Gulshoda Sobir kizi; Karimov Olim Rasulovich (Zien Journals, 2022)
Diabetes and similar nutritional diseases, which are now spreading around the world, have been included in the list of global medical and social problems of the XXI century by the World Health Organization. According to statistics from the International Diabetes Federation, the number of people with diabetes in the world in 2019 will reach 463 million and is increasing among children and adolescents. Many illnesses are caused by eating disorders. Malnutrition is a common cause of metabolic, cardiovascular, and digestive disorders. Violation of the principles of rational nutrition is observed when the required amount of nutrients, vitamins and minerals is below or above the norm.
Keywords: nutrition; illnesses; minerals; rural